Faktor Yang Berhubungan dengan Computer Visual Syndrome (CVS) Pada Karyawan di Departement of Design Center Directorat Technologi PT Dirgantara Indonesia - Mauliku, Novie; Sofian, Rizki (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2022)
Exorbitant PC use can affect eye wellbeing. An assortment of eye side effects experienced while working with PCs is called PC vision disorder (CVS). Factors connected with the frequency of CVS incorporate interior and outer variables. This study expects to decide the gamble factors related with CVS occasions in workers at the Branch of Configuration Center Innovation Directorat PT. Indonesian Aviation. The examination strategy utilized cross-sectional with a complete example of 56 respondents still up in the air through purposive testing. Information were gathered through interviews utilizing a poll and examined by univariate and bivariate utilizing Chi Square Test. The outcomes showed that 32% of representatives experienced CVS with a typical period of north of 40 years as much as 52%, 59% work breaks and 80% separation from standard screens, yet the force of lighting in the work area was not suitable, to be specific 66%. The consequences of measurable tests showed that there was no connection betwen age (p = 0.106), work breaks (p = 0.950) and screen distance (p = 0.146), however there was a relationship with lighting force (p = 0.029) with the occurrence of CVS in representatives in the Branch of Wellbeing. of Configuration Center Directorat Innovation PT. Indonesian Aviation. All in all, the gamble factor with CVS occasions in this study is lighting, so the proposal that can be given is to change the degree of lighting in the work area as per the work exercises.